Remote Sensing in Vessel Detection and Navigation - Heiselberg, Henning; Stateczny, Andrzej (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Special Issue entitled "Remote Sensing in Vessel Detection and Navigation" comprises 15 articles on many topics related to remote sensing with navigational sensors. The sequence of articles included in this Special Issue is in line with the latest scientific trends. The latest developments in science, including artificial intelligence, were used. It can be said that navigation and vessel detection remain important and hot topics, and a lot of work will continue to be done worldwide. New techniques and methods for analyzing and extracting information from navigational sensors and data have been proposed and verified. Some of these will spark further research, and some are already mature and can be considered for industrial implementation and development.